Financial Risk Management Analysis in Addressing Market Volatility in the Era of Global Digital Transformation - Ardiyatur Rahman; Yoyo Sudaryo; Nunung Ayu Sofiati; Andre Suryaningprang; Riyandi Nur Sumawidjaja (JURNAL ECONOMINA, 2026)
This study aims to analyze financial risk management in the face of market volatility in the era of global digital transformation. The research approach applied is a literature-based study, which relies on written sources as the primary basis for data collection and analysis. The systematic compilation of relevant information is carried out through a review of various scientific literature, including books, journals, articles, research reports, and other relevant literature. The collected information is processed using a content analysis approach to identify certain patterns, relationships, and important information related to financial risk management, digital market volatility, and global digital transformation. The results show that digital transformation has increased market connectivity, accelerated the flow of information, and given rise to various new risks that contribute to increased market volatility. Financial risk management plays a crucial role in identifying, measuring, and controlling these risks through the use of technology, strengthening governance, and adaptive mitigation strategies. This study confirms that the implementation of digital technology into risk management systems is a crucial factor in maintaining financial stability and increasing organizational resilience amidst increasingly complex global market dynamics.